PERANCANGAN BUKU CERITA BERGAMBAR SEJARAH PERJUANGAN RAKYAT GADUT MENGHADAPI PENJAJAH BELANDA UNTUK ANAK USIA 9-12 TAHUN DI BUKITTINGGI - Tegar Setiadi, Drs. Mediagus, M. Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The Avro RI-003 aircraft monument is a testament to the history of the Gadut struggle and its surroundings against the Dutch occupiers. The historical evidence of the struggle has been forgotten by the public. Lack of public appreciation of history is because people are reluctant to remember and remember the history of the people's struggle. Most of them assume that history is just part of the past and boring to remember. Many young people in Bukittinggi city especially children 9-12 years old do not know the history of the struggle. Adults, and teens, too, feel saturated with history as history has only been conveyed in the form of books dominated by writing.Keywords: Design, History, Picture Story, Media